Computational Studies of Donepezil and Acetylcholinesterase Dynamics Interactions - Windah, Axl Laurens Lukas; Istyastono, Enade Perdana (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Donepezil is an acetylcholinesterase (AChE) inhibitor commonly used as an anti-dementia medication for patients with Alzheimer's Disease. This research aims to determine the stability of each enantiomer R and S of donepezil as an AChE inhibitor using molecular dynamics (MD) simulations. The MD simulations were performed on a Cloud Protein Simulator (CPS) with YASARA-Structure as the main software and PyPLIF HIPPOS as the software to identify protein-ligand interactions. The MD simulations were performed in three replications of 50 ns for each enantiomer complexed to AChE. The stabilities of the AChE-donepezil complexes were analyzed by assessing the root-mean-squared deviation (RMSD) values of the AChE backbone atoms (RMSDBb) and the ligand (RMSDLigMov) during the last 5 ns of simulation time. The dynamics of the protein-ligand interactions were also analyzed during the last 5 ns. The results of these MD simulations indicate that the S-donepezil serves as a better AChE inhibitor compared to the R-donepezil.